Change of blood flow in common carotid artery during physical exercise stress: evaluation for aerobic exercise intervention - Noor Azmi, Azran Azhim; Yohsuke, Kinouchi (Nova Science Publisher, 2010)
Exercise training is able to alter cardiovascular fitness. Treadmill exercise testing currently is commonly used in the clinical method of evaluating a subject's functional capacity and aerobic fitness. In this chapter, a fundamental understanding of age-associated normohemodynamic state is described for comparison data and for an improved means of aerobic exercise fitness and performance. These data may contribute to effective and efficient prevention and treatment of cardiovascular disease in older persons. The change of blood flow velocity and parameters in the common carotid artery (CCA) during treadmill exercise is reviewed to describe the effect on significant physiological functions. Increase of blood flow velocity and its parameters in CCA during physical exercise is related to increase of arterial blood pressure (ABP), which may be due to elevation of the cerebral perfusion pressure and then contribute in part to the increase in cerebral blood flow (CBF). Aerobic exercise training could improve the age-associated decreases in blood flow velocity waveforms of CCA after a 1-month exercise intervention program. Regular aerobic exercise training is an effective approach to diminish the age-associated decrease in CCA blood flow velocities in healthy older adults and partially restore the reductions of blood flow velocity in previously sedentary young men. The potential benefit of regular physical activity would be in the primary prevention of age-associated decreases in blood velocity waveforms. © 2010 by Nova Science Publishers, Inc. All rights reserved.